Implications of European Union enlargement for CARICOM countries - Greenaway, David (Caribbean RNM/IDB Project Christ ChurchBB, 2001)
Seeks to inform the Regional Negotiating Machinery's position with the EU on post-Lomé trade, investment and development arrangements.